Activated Sludge Technology to Treat Wastewater from Offices and Residential Areas PT Kaltim Prima Coal - Kris Pranoto; Widia Rahmawati Pahilda; Muhammad Sonny Abfertiawan; Apridawati Elistyandari; Andi Sutikno (Indonesian Mining Professionals Journal, 2019)
In Indonesia, coal mining operations generally involve a huge number of workers. This condition causes its own challenges in managing environmental impacts that potentially generated from human activities. One of them is domestic wastewater. Domestic waste water is waste water that comes from activities of daily living of humans related to water usage. In mining operations, domestic wastewater is generated from office and residential areas. Because of the potential impact on the environment, domestic wastewater must be treated before flowing to natural water bodies. Since the beginning of mining operations in 1990s, PT Kaltim Prima Coal has been building and operating Domestic Wastewater Treatment Plant (IPALD) to treat domestic wastewater resulting from offices and residential areas. There are 12 IPALDs with activated sludge technology operating in the PT KPC area. Active sludge is one of the domestic wastewater treatment technologies by utilizing the role of aerobic bacteria to degrade organic material contained in domestic wastewater. This paper is presented to describe the performance of activated sludge technology usedin the KPC’s IPALD and the challenges faced in its operation. One of the challenges faced is the fulfillment of water quality standards in Minister of Environment and Forestry Decree No. P. 68 of 2016 concerning Domestic Wastewater Quality Standards. The latest quality standards regulate the effluent concentration of IPALD more stringent than before and there are new parameters, including ammonia which requires attention in the operation of IPALD.